Comparison of the proteomic landscape in experimental ischemia reperfusion with versus without ischemic preconditioning - Yalda Kakaei; Shafaat Hussain; Ahmed Elmahdy; Evelin Berger; Aaron Shekka Espinosa; Valentyna Sevastianova; Zahra Sheybani; Amin Al-Awar; Mana Kalani; Sandeep Jha; Ermir Zulfaj; Amirali Nejat; et al. (Scientific Reports)
Abstract Myocardial ischemic preconditioning (IPC) enhances myocardial resilience to ischemic injury. Myocardial stunning is a transient, reversible dysfunction, while necrosis involves irreversible cell death. The relationship between IPC, stunning, and necrosis is not well understood, requiring further molecular investigation. This study aimed to investigate the proteomic changes associated with IPC, focusing on its relationship with myocardial stunning and necrosis. A novel 13.5-minute ischemia-reperfusion (I/R) rat model was specifically chosen to induce myocardial stunning, providing a unique approach to assess IPC effects in this context. Rats underwent either IPC with two 5-minute ischemia/reperfusion cycles followed by a 13.5-minute ischemic period or the procedure without IPC (no ischemic preconditioning, NIPC). Myocardial samples were collected at early (T1) and 4-hour post-reperfusion (T2) time points for proteomic analysis. Protein levels were quantified by differential labeling using TMTpro reagents, and subsequent liquid chromatography–mass spectrometry. IPC induced upregulation of proteins involved in endocytosis and Fc gamma R-mediated phagocytosis pathways at T1, while downregulating proteins related to tissue remodeling, immune response, and coagulation at T2. Conversely, NIPC exhibited upregulation of proteins associated with tissue damage and inflammation. IPC rats demonstrated enhanced leukocyte migration, complement activation, and immune response between T1 and T2. Consistent proteomic changes were observed between T1 and T2 in IPC vs. NIPC groups, and common alterations between IPC T2 vs. T1 and NIPC T2 vs. T1 comparisons underline shared pathways in cardiac complement and coagulation cascades. Our study reveals distinct proteomic changes induced by IPC in the context of myocardial stunning and necrosis. IPC activates early protective pathways, attenuates tissue damage and inflammation, and preserves myocardial function. These findings underscore IPC’s reparative potential and identify myocardial stunning as an important, transient adaptation, which may have implications for supportive clinical management in I/R.